2018
DOI: 10.1155/2018/2630565
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Medium Chain Triglycerides on Time to Nutritional Ketosis and Symptoms of Keto-Induction in Healthy Adults: A Randomised Controlled Clinical Trial

Abstract: Medium chain triglycerides (MCTs) are ketogenic and might reduce adverse effects of keto-induction and improve time to ketosis and the tolerability of very low carbohydrate diets. This study investigates whether MCT supplementation improves time to nutritional ketosis (NK), mood, and symptoms of keto-induction. We compared changes in beta-hydroxybutyrate (BOHB), blood glucose, symptoms of keto-induction, and mood disturbance, in 28 healthy adults prescribed a ketogenic diet, randomised to receive either 30 ml … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 42 publications
1
46
1
1
Order By: Relevance
“…Ketosis may ideally be described as a continuous variable, but certain cut-off points may be useful in clinical or scientific settings. BHB ≥0.5 mmol/L, measured by capillary finger pricks, has been used as a cut-off for ketosis clinically (23) and as a research outcome (5,24). As previously reported (21), exploratory analyses on our data revealed that a cut-off at 0.5 for capillary blood corresponded to 0.3 in venous blood (the outcome of the current article).…”
Section: Discussionsupporting
confidence: 65%
“…Ketosis may ideally be described as a continuous variable, but certain cut-off points may be useful in clinical or scientific settings. BHB ≥0.5 mmol/L, measured by capillary finger pricks, has been used as a cut-off for ketosis clinically (23) and as a research outcome (5,24). As previously reported (21), exploratory analyses on our data revealed that a cut-off at 0.5 for capillary blood corresponded to 0.3 in venous blood (the outcome of the current article).…”
Section: Discussionsupporting
confidence: 65%
“…Reported timing of symptoms was typically within several days of starting KD, peaked in the first week and dwindling after 4 weeks. The range of symptoms reported in online forums compares with Harvey's RCT of KD with and without dietary supplementation with medium-chain triglycerides (MCT) in healthy adults (N = 28), examining the effect of MCT on the incidence and duration of keto-induction (23). The authors used a 5-point Likert scale to assess the occurrence of symptoms/effects of KD in a period of 20 days.…”
Section: Discussionmentioning
confidence: 99%
“…Side effects were associated with higher levels of ketosis (9). In adults, two reviews (21,22) and two empirical studies (14,23) have noted short term adverse effects of KD including gastrointestinal, muscular, and nervous system symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…The divergence of our results from the data reported in the literature, could be explained by the different type of absorption that exists between medium hydrocarbon chain fatty acids (MCFAs) and LCFAs. MCFAs do not require the action of bile salts nor the absorption mediated by micelles and chylomicrons contrary to what occurs for LCFA absorption [ 59 ]. The increase in SFA, consisting of medium hydrocarbon chain, could derive from the absorption without bile salts which decreases in conditions of liver lipidosis [ 15 ].…”
Section: Discussionmentioning
confidence: 99%